PEMBUATAN SABUN MANDI PADAT DARI MINYAK JELANTAH DAN BIJI KAKAO (Theobroma cacao L.) - Suaedi; Nurasia; Puspita Sari (Cokroaminoto Journal of Chemical Science, 2019)
This research aims to make solid soap from used cooking oil and cocoa beans (Theobroma cacao L.). This research was conducted in the laboratory of natural materials at the Faculty of Science, University of Cokroaminoto Palopo. The process of making soap through several stages, namely the first stage of purification, neutralization and bleaching of used cooking oil using bleaching Earth and testing of free fatty acid levels (FFA). Purification results obtained with different variations of the stirring contact time showed good results with a decrease in free fatty acid levels in used cooking oil. The results of the analysis of fatty acid levels are calculated based on palmitic acid, lauric acid and oleic acid. The second stage is the manufacture of solid bath soap and continued with testing the quality of the soap. There are two types of soap quality testing, namely the pH test and the free alkali test. The test results showed that the pH of soap with the addition of NaOH solution with a concentration of 20%, 30% and 40% was 12. The pH level of the resulting soap did not meet the standards. The results of testing alkaline free soap bath with a concentration of 20% NaOH obtained by 22.6%, soap with a concentration of 30% NaOH of 28.92% and bath soap with a concentration of 40% NaOH of 1.66%. The results obtained are still not in accordance with the soap quality standards set by SNI.